Prevention and therapy of preterm birth: guideline of the DGGG, OEGGG and SGGG (S2k level, AWMF registry number 015/025, February 2019) - part 1 with recommendations on the epidemiology, etiology, prediction, primary and secondary prevention of preterm birth = Prävention und Therapie der Frühgeburt : Leitlinie der DGGG, OEGGG und SGGG (S2k-Niveau, AWMF-Registernummer 015/025, Februar 2019) - Teil 1 mit Empfehlungen zur Epidemiologie, Ätiologie, Prädiktion, primären und sekundären Prävention der Frühgeburt - Berger, Richard; Fluhr, Herbert; Kuon, Ruben-Jeremias; Schütz, Florian (Geburtshilfe und Frauenheilkunde, 2019)
Aims This is an official guideline of the German Society for Gynecology and Obstetrics (DGGG), the Austrian Society for Gynecology and Obstetrics (ÖGGG) and the Swiss Society for Gynecology and Obstetrics (SGGG). The aim of this guideline is to improve the prediction, prevention and management of preterm birth based on evidence obtained from recent scientific literature, the experience of the members of the guideline commission and the views of self-help groups. Methods Based on the international literature, the members of the participating medical societies and organizations developed Recommendations and Statements. These were adopted following a formal process (structured consensus conference with neutral moderation, voting was done in writing using the Delphi method to achieve consensus). Recommendations Part I of this short version of the guideline lists Statements and Recommendations on the epidemiology, etiology, prediction and primary and secondary prevention of preterm birth.
Gesehen am 20.12.2019